PREDICTION OF BIOMASS OF SPOTTED SARDINE (Amblygaster sirm) IN THE JAVA SEA - Suherman Banon Atmaja; Bambang Sadhotomo (Research Center for Fisheries, 2006)
Biomass of spotted sardine (Amblygaster sirm) has been predicted using biomass dynamics model and cohort analysis. These methods can predict behaviour biomass to impact of exploitation.